Consumption, nutrient digestibility and lactation performance of dairy cows fed soybeans in different forms - Vasconcelos, Angela Maria de; Valadares Filho, Sebastião de Campos; Dias, Marcia; Nascimento, Vinicio Araujo; Façanha, Débora Andréa Evangelista; Fernandes, Juliano José de Resende (Semina: Ciências Agrárias, 2015)
Twelve Holstein cows were given diets containing soybean supplied in different ways in order to identify possible changes in lactation performance and evaluate the economic feasibility of the diets. The diets included&58; soybean meal only (SM-control)&59; raw soybean (RaS)&59; roasted soybean (RoS) and soybean meal plus 5% urea (SMU). The forage consisted of corn silage. We analyzed the dry matter intake, milk production and collected milk samples. To estimate digestibility, we collected six samples of feces over a period of six consecutive days. The intake of dry matter (DM), organic matter (OM), neutral detergent fiber (NDF) and non-fiber carbohydrates (NFC) did not differ among treatments. On the other hand, crude protein (CP) intake was influenced by the diets, and the highest mean values of ether extract (EE) were found with the RaS and RoS diets. The intake of total digestible nutrients (TDN) was lower in the RaS and RoS diets compared to the control diet. DM, OM, CP, EE, and NDF digestibility were not affected by the different diets, while NFCs were reduced in the RoS diet and TDN decreased with both the RaS and RoS diets. There were also no differences observed across diets for total milk production, production corrected to 3.5% fat, diet efficiency, or milk per kilogram of dry matter and/or crude protein. We conclude that raw and roasted soybeans as well as concentrate plus 5% urea in dry matter may be used instead of soybean meal as feed for high-producing cows, without affecting milk production and composition. We also observed that the SMU diet was the least costly.

Utilizou-se 12 animais da raça Holandesa para avaliar o efeito de dietas contendo soja fornecida de diferentes formas e obter informações sobre possíveis alterações no desempenho lactacional como também verificar sua viabilidade econômica. As dietas constituíam-se de farelo de soja exclusivo (FS-controle); soja crua (SC); soja tostada (ST) e farelo de soja mais 5% de uréia (FSU). O volumoso foi à silagem de milho. Foram registrados consumo de matéria seca, produção de leite e colhidas amostras de leite. Para estimativa da digestibilidade foram coletadas seis amostras de fezes durante seis dias consecutivos. Os consumos de matéria seca (MS), matéria orgânica (MO), fibra detergente neutra (FDN) e carboidratos não fibrosos (CNF) não diferiram. O consumo de proteína bruta (PB) foi influenciado pelas dietas e as maiores médias de extrato etéreo (EE) foram com a SC e ST. O consumo dos nutrientes digestíveis totais (NDT) foi menor com a inclusão da SC e ST em relação à dieta controle. A digestibilidade da MS, MO, PB, EE, FDN não foram afetados e o CNF foi reduzido com ST e do NDT diminuiu com SC e ST. A produção total de leite e corrigida para 3,5% de gordura, sua eficiência e leite por quilograma de matéria seca e/ou proteína bruta não diferiram. Os grãos de soja crus e tostados como também concentrado adicionado de 5% de ureia na matéria seca podem ser usados como alternativas na alimentação de vacas de alta produção em substituição ao farelo de soja sem prejuízo para a produção e composição do leite. A dieta com FSU teve menor custo.
Keywords: Milk constituents; Processing methods; Metabolizable protein; Economic viability